The Beard-Mackie Sight-Indicator for the Measurement of Marsh-Gas in Collieries - M. H. HARRINOTON (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1906)
THE Transactions of the Institute afford abundant evidence of the general recognition by mining engineers of the importance of a safety-lamp which will not only give warning of the presence of fire-damp, but will also indicate the proportion in which it is present.' Mining-men are only too familiar with the frequent and sudden changes that constantly occur at the working-face of a gaseous mine. Nothing illustrates more forcibly the pregnant condition of the strata enfolding the seam and the seam itself, than the fact that a circulation of perhaps 150,000 cu. ft. of air may contain 2 or even 3 per cent. of marsh-gas, representing a volume of from 3,000 to 4,000 cu. ft. of this gas pouring-out each minute from the natural strata into the mine-workings. It would, indeed, be strange if this great outflow of gas were always constant, and it creates no surprise that such earth-breathings, as they may be called, are spasmodic and irregular in their wane and flow. There are other causes that act to vary the gaseous condition of mine-air. Gas has a tendency, often very manifest in mine-workings and airways, to stratify and, at times, to travel long distances in veins or streams. It is common to catch and lose the gas in the lamp when making a test. At times two lamps, held side by side in an air current, will indicate different gaseous conditions of the passing air. When testing for gas, the lamp may suddenly fill with flame, in a mine-chamber, where a moment before a careful test showed the presence of but 1 per cent. of gas. It is sometimes remarked that there is little need of detecting a smaller percentage of gas than is revealed by the common